Forest incomes and poverty alleviation under participatory forest management in the Bale Highlands, Southern Ethiopia - Yemiru, T.; Roos, A.; Campbell, Bruce M.; Bohlin, F. (2010)
There is an increasing interest in understanding the role forest products and forest resource management in rural livelihoods and poverty reduction strategies. This study investigates the contribution of forest resources to the livelihoods of rural households under a participatory management arrangement in southern Ethiopia. Data were collected through key informant interviews, group discussion, and household surveys from a total of 350 households. Income data were collected in four separate seasons at intervals of three months. The result indicates that forest products are the most important sources of income contributing to 34% and 53% of household per capita income and per capita cash income, respectively. Forest income also helps 20% of the population to remain above the poverty line. Forest income reduces inequality (Gini coefficient) by 15.5%. In general, the result confirms the importance of forest income in poverty alleviation and as safety nets in times of income crisis.